Z-plasty and Postoperative Radiotherapy for Anterior Chest Wall Keloids: An Analysis of 141 Patients. Issue 3 (March 2019) - Arima, Juri; Dohi, Teruyuki; Kuribayashi, Shigehiko; Akaishi, Satoshi; Ogawa, Rei
Abstract : Background: The therapies for anterior chest wall keloids include surgical excision, postoperative radiotherapy, silicone taping stabilization, and steroid plaster. However, to date, there is no universally accepted combination treatment strategy for anterior chest wall keloids. Methods: All consecutive patients with single or multiple anterior chest wall keloids who underwent keloid excision, tension-reducing suturing, z-plasty, and postoperative radiotherapy in 2013–2016 in Nippon Medical School were included in this case series study. Only keloids that arose from small injuries such as folliculitis or acne were selected. The surgery was followed by tension-reducing self-management of the wounds with silicone tape and steroid plaster. The postsurgical radiotherapy modality was 18 Gy administered in 3 fractions over 3 days. The primary study outcome was keloid recurrence during the 24-month follow-up period. Recurrence was defined as the development of stiff and red lesions in even a small part of the scar that did not respond to 6 months of steroid plaster therapy. Results: In total, 141 patients with 141 lesions were enrolled. Of the 141 lesions, 15 (10.6%) recurred. All recurrences were successfully treated by steroid plaster and steroid injection. The recurrence patients did not differ from the nonrecurrence patients in terms of the size of the original keloid or gender distribution. Conclusions: Anterior chest wall keloids can be successfully treated by customized plans that involve appropriate surgical modalities (including z-plasty) followed by postoperative radiotherapy (18 Gy in 3 fractions over 3 days) and scar self-management with silicone tape and steroid plaster.